Lnvestlgations on some biochemical parameters and milk.yleld in dairy cows fed supplemental β-carotene - Mehmet NİZAMLIOĞLU; Ali Muhtar TİFTİK; Kürşat IŞIK (Eurasian Journal of Veterinary Sciences)
In this study, same bioch,emical values and milk production were in vestigated in dairy cows· fed supplemental β-carotene. A total of 12 Swedish Red Cows were used as materials. Animal were divided two equal groups. Group 1; given β-carotene periods of 5 weeks (1 gr/dy/each cow). Group 2; control group. β-carotene, ALP and GOT were determined in blood samples. Daily milk yield was measured for 4 months. β-carotene and GOT values were changed statistically (P<0.05; P<0.01) in experimental and control groups respectively. The differences of the average of milk production in groups increased after giving β-carotene.